Strategic competencies of bumiputera SME owners in Melaka Tengah district / Mohd Nazir Rabun and Ahmad Syahreen Jailani - Rabun, Mohd Nazir; Jailani, Ahmad Syahreen Jailani (Faculty of Administrative Science and Policy Studies, 2011)
This paper focuses on the strategic competencies of the small and medium enterprises (SMEs) owners. The aim is to identify the level of the competencies of Bumiputera SME owners in Melaka Tengah District. The empirical data consisted of 46 Bumiputera SME owners in that area. The data are analysing based on the stage in the strategic competencies which are strategy formulation, strategy implementation and strategy evaluation. The results suggest that the owners are not too competent with the strategy evaluation competency. The results increase our understanding on the strategic competencies level of Bumiputera SME owners in Melaka Tengah District.